A Retrospective Analysis on Clinical Practice-Based Approaches Using Zolpidem and Lorazepam in Disorders of Consciousness - Bei Zhang; Katherine O’Brien; William Won; Sheng Li (Brain Sciences, 2021)
This is a retrospective study to investigate the results of using zolpidem and lorazepam in persons with disorders of consciousness (DoC) and to provide practical information for clinical application and further studies. The cohort included 146 patients (11 hemorrhagic stroke, 87 traumatic brain injury (TBI), 48 anoxic brain injury (ABI)) admitted to a specialized DoC rehabilitation program. A positive trial indicated a patient responded to either zolpidem or lorazepam with prominent functional improvements necessitating routine use of the medication. Non-responders had equivocal or negative (i.e., went to sleep) responses. Eleven patients with a stroke who had either medication were all non-responders. Of the remaining 135 patients, 95 received at least one medication trial. The overall positive rate was 11.6% (11/95), with 6.3% (5/79) for zolpidem and 14.0% (6/43) for lorazepam. Among TBI patients, the positive rate of the zolpidem trial (10.2%, 5/49) was slightly higher than that of the lorazepam trial (6.9%, 2/29; p > 0.05). Among ABI patients, the positive rate of the lorazepam trial (28.6%, 4/14) was significantly higher than that of the zolpidem trial (0%, 0/30; p = 0.007). Following a positive trial, most patients were continued on the medications on a regular basis before eventual discontinuation. Our results suggested the etiology of DoC, considering traumatic vs. anoxic injuries, may serve in guiding the clinical application of these medications in the treatment of DoC and in future prospective studies. We advocate for screening all patients with DoC using zolpidem and/or lorazepam.